Filosofia e arte em Theodor W. Adorno: a categoria de constelação - Eduardo Soares Neves Silva (2006)
This thesis states that the category of constellation is the key of what Adorno calls thought models and, as such, guarantees the loyalty to his utopia of knowledge. In doing so, it challenges in fruitful way two interpretation problems: the one that questions its actuality and the other that looks for the connection between art and philosophy. It concludes that the constellation, as methodical procedure and compositional principle, illuminates the connection between both and elucidates themeaning of Adornos actuality, by way of attesting the significance of the notions of time diagnosis, determinate negation, dialectical moment and composition.